Design and analysis of a public key infrastructure for SBAS data authentication. Issue 4 (14th January 2020) - Neish, Andrew; Walter, Todd; Powell, J. David
Abstract: Integral to any authentication system is the design of its public key infrastructure (PKI), allowing the system to distribute, maintain, and revoke cryptographic keys while dividing and allocating the responsibility of security between different entities. This paper develops a PKI for two SBAS candidate authentication schemes: one each for an L5 I‐channel and Q‐channel implementation. A simulator, introduced as MCOS, is developed to enable large scale Monte Carlo tests of these PKI designs. This work concludes that once a receiver has been deployed with a set of preinstalled encrypted public keys, a strictly over‐the‐air method of delivering PKI information is feasible for SBAS data authentication in nominal conditions. This work also provides a strong candidate PKI that is designed to be standardized internationally for current and future SBAS service providers.